2021
DOI: 10.1055/a-1581-6881
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Cardiac Arrhythmias

Abstract: Since the coronavirus disease (COVID-19) pandemic spread unrelentingly all over the world, millions of cases have been reported. Despite a high number of asymptomatic cases, the course of the disease can be serious or even fatal. The affection of the myocardium, called myocardial injury, is caused by multiple triggers. The occurrence of cardiac arrhythmias in COVID-19 patients with myocardial involvement and a critical course is common. In this review, potential mechanisms, incidence, and treatment options for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
0
14
0
5
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is a systemic disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has been affecting millions of people around the world since December 2019 ( 1 , 2 ). SARS-CoV-2 can cause damage to multiple organs ( 3 ). Detailed mapping of the viral RNA in tissues of 11 deceased patients with COVID-19 has shown cardiovascular dissemination of the virus in all patients ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is a systemic disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has been affecting millions of people around the world since December 2019 ( 1 , 2 ). SARS-CoV-2 can cause damage to multiple organs ( 3 ). Detailed mapping of the viral RNA in tissues of 11 deceased patients with COVID-19 has shown cardiovascular dissemination of the virus in all patients ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The median QTc observed at the CHUL could reflect a greater sensitivity of this population to treatment. Some authors showed that cardiac arrythmias in COVID-19 patients with severe or critical disease or with myocardial impact also involve QTc prolongation, while others found that QTc prolongation is rare during COVID-19 but drugs like HCQ and azithromycin are associated with a significant risk of QTc prolongation in SARS-CoV2 infected persons; this risk increases when azithromycin is associated with HCQ [ 23 , 24 , 25 ]. Additionally, COVID-19 patients were shown to be more susceptible to drug-induced QTc prolongation [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis requires further investigation [20,21]. Theoretically, the mechanisms of cardiac cell injury are hypoxia, myocarditis, myocardial ischemia, or abnormal host immune responses that induce cardiac arrhythmias due to direct viral invasion and inflammation that can result in unstable myocardium and cell membranes and can influence QTc prolongation in COVID-19 [2,22].…”
Section: Sd: Standard Deviationmentioning
confidence: 99%